Antibacterial And Synergistic Effect Of Medicinal Herbs As Potential Activity Against Antibiotic Resistant–Bacteria : A New Strategy For Control Or Reducing Antibiotic Resistant Bacteria (Journal of Pharmaceutical Negative Results, 2022)
Drug resistance in bacteria became great global problem .this review suggested to use medicinal herbs to increase susceptibility toantibiotics as a new strategy for control of antibiotic resistance. The proliferation of bacteria that are resistant to antibiotic treatmentposes a substantial challenge to the development of effective treatments for microbial infections. The prospect of humans returning to atime before the widespread use of antibiotics has caused scientists to express growing anxiety. Therefore, it is essential to look for otherways to combat germs in today's world. Certain bacteria have the ability to withstand antibiotic treatment of their own accord, whereasother bacteria develop resistance to antibiotics due mostly to the improper use of antibiotics and the development of new resistantversions through mutation. Plants have been a primary source of both conventional pharmaceuticals and alternative medicines for treatinga wide variety of ailments ever since ancient times. Secondary metabolites such as alkaloids, quinones, tannins, terpenoids, flavonoids,and polyphenols are abundant in plant foods because plants are such a rich source of these compounds. Numerous studies haveconcentrated their attention on the secondary metabolites of plants as a possible source of antibiotics. They possess the necessarystructural qualities and are capable of acting via a variety of methods. There are many applications of medicinal plants including ,antibacterial , antifungal , antiviral , anti-depression , antioxidant , anti-inflammatory , anti-insecticidal because plant posses many activecompounds . Eucalyptus contain Cineole as active compounds with area 85.82 %. Lemongrasses possess Geranial with area 34%. Clovecontain euganol with 85% area. rosemary possess cineol with 23% area .